2017
DOI: 10.1590/1982-021620171954017
|View full text |Cite
|
Sign up to set email alerts
|

Dysarthria and quality of life in patients with amyotrophic lateral sclerosis

Abstract: Purpose: to analyze the impact of dysarthria on the quality of life in patients with amyotrophic lateral sclerosis.Methods: the study consisted of 32 subjects, divided into two groups (control group and study group) who underwent an initial interview for background information, followed by an evaluation based on the Dysarthria Assessment Protocol and completion of quality of life questionnaire "Living with Dysarthria -(LwD)". Exploratory data analysis was collected through mean, median, SD, minimum and maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 13 publications
3
35
0
4
Order By: Relevance
“…Leite Neto and Constantini (2017) reported that a reduction in natural speech increases the risk of social withdrawal and reduced QoL with other researchers showing the changes in relationships that occur between plwMND and significant others is devastating (Gauthier et al . 2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Leite Neto and Constantini (2017) reported that a reduction in natural speech increases the risk of social withdrawal and reduced QoL with other researchers showing the changes in relationships that occur between plwMND and significant others is devastating (Gauthier et al . 2007).…”
Section: Discussionmentioning
confidence: 96%
“…2012). There is evidence of a correlation between the increase in speech difficulties experienced by plwMND and a reduction in their quality of life (QoL) (Leite Neto and Constantini 2017).…”
Section: Speech and Identitymentioning
confidence: 99%
“…It is believed that there are several factors that may contribute to the onset of the disease, such as excitotoxicity by neurotransmitter glutamate, accumulation of neurofilaments, deficiency of neurotrophic factors, immunity changes, physical trauma, and persistent viral infections, as well as chemical and physical environmental factors [54]. With the progress of the disease, communication difficulties increase while sentences become simpler and shorter, culminating, in advanced phases, to answering questions through the use of keywords or “yes/no” answers [55]. These changes, together with the loss of functional independence caused by ALS, lead to an extremely discouraging situation for the individual.…”
Section: Discussionmentioning
confidence: 99%
“…Amyotrophic Lateral Sclerosis (ALS) is a heterogeneous neurodegenerative disease that results in disorders in the motor skills, cognition and behavior, highlighting serious problems in the individual´s functional skills, thus, limiting his/her possibilities of social interaction [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…Speech motor disorders in individuals with ALS have been described over the years, with more intensity and frequency in those individuals who show bulbar onset symptoms 2,4 . They are present in more than 80% of the cases at some point of the disease, and 75-95% of patients lose their oral communication skills 5 .…”
Section: Introductionmentioning
confidence: 99%